Dasar-Dasar Ontologis Pemahaman Hermeneutik Hans-Georg Gadamer - Agus Darmaji (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2013)
Hans-Georg Gadamer explicitly agrees with Heidegger that ‘Being’ is always been understood through the language and the dimension of time. So to catch up the Being, we need to know the Being itself, and to understand it. To understand means to perceive within the time and historicity. This paper will make clear the ontological basics of Gadamer’s hermeneutics containing: the relationship between historical aspect and understanding; hermeneutic discourse and sequential distance; prejudice and understanding; effective historical consciousness; understanding as application; and the structure of questions and answers.DOI: 10.15408/ref.v13i4.911